A Nanoparticle-Based Biosensor Combined With Multiple Cross Displacement Amplification for the Rapid and Visual Diagnosis of Neisseria gonorrhoeae in Clinical Application - Chen, Xu; Huang, Liming; Zhou, Qingxue; Tan, Yan; Tan, Xuhong; Dong, Shilei (Frontiers in Microbiology, 2021)
Gonorrhea is a sexually transmitted disease caused by the host-adapted human pathogen, Neisseria gonorrhoeae. The morbidity is increasing and poses a major public health concern, especially in resource-scarce regions. Therefore, a rapid, visual, sensitive, specific, cost-saving, and simple assay for N. gonorrhoeae detection is critical for prompt treatment and the prevention of further transmission. Here, for the first time, we report a novel assay called the multiple cross displacement amplification combined with gold nanoparticle-based lateral flow biosensor (MCDA-LFB), which we constructed for the rapid and visual identification of N. gonorrhoeae in clinical samples. We successfully devised a set of MCDA primers based on the N. gonorrhoeae-specific gene, orf1. Optimal assay conditions were determined at 67°C, including genomic DNA preparation (∼15 min), MCDA amplification (30 min), and LFB reading (∼2 min), which can be completed within 50 min. The limit of detection (LoD) of the assay was 20 copies/test (in a 25-μl reaction mixture). Assay specificity was 100%, with no cross-reactions with other pathogens. Thus, our N. gonorrhoeae-MCDA-LFB is a rapid, specific, visual, cost-saving, and easy-to-use assay for N. gonorrhoeae diagnostics, and may have great potential for point-of-care (POC) testing in clinical settings, especially in resource-limited regions.